Design of a Meeting Room Air Conditioning System Based on Fuzzy Logic Control - Mohammad Harry Khomas Saputra; Ridwan; Nenden Siti Nurkholipah; Siti Hadiaty Yuningsih; Marta Hayu Raras Sita Rukmika Sari; Aan Setiawan (Politeknik META Industri Cikarang, 2026)
Background Conventional room cooling systems generally operate at fixed fan speeds without considering variations in room temperature and occupant density, leading to reduced thermal comfort and inefficient energy consumption Purpose This study aims to design and implement an automatic room cooling system that adjusts fan speed based on room temperature and visitor density using Mamdani fuzzy logic control. Methodology The system integrates a DHT22 sensor to measure room temperature and an ultrasonic sensor to estimate visitor density. Mamdani fuzzy logic was employed to process linguistic variables for temperature (